Analysis photo of the year 2006 Indonesian press photo award based on the three visual layers theory - Prasetyo, Andry; Guntur, Guntur; Ajidarma, Seno Gumira; Soewarlan, Santosa (Institut Seni Indonesia Surakarta, 2024)
This article aims to analyze the work of the 2016 Indonesian Press Photo Award Photo of the Year entitled